Visualization of the biochemical markers of atherosclerotic plaque with the use of Raman, IR and AFM. Issue 9 (7th March 2014) - Marzec, Katarzyna M.; Wrobel, Tomasz P.; Rygula, Anna; Maslak, Edyta; Jasztal, Agnieszka; Fedorowicz, Andrzej; Chlopicki, Stefan; Baranska, Malgorzata
Abstract In this work, we describe a methodology to visualize the biochemical markers of atherosclerotic plaque in cross sections of brachiocephalic arteries (BCA) taken from ApoE/LDLR–/– mice. The approach of the visualization of the same area of atherosclerotic plaque with the use of Raman, IR and AFM imaging enables the parallel characterisation of various features of atherosclerotic plaques. This support to the histochemical staining is utilized mainly in studies on mice models of atherosclerotic plaques, where micro and sub‐micro resolutions are required. This work presents the methodology of the measurement and visualization of plaque features important for atherosclerosis development and plaques vulnerability analysis. Label‐free imaging of cholesterol, cholesteryl esters, remodeled media, heme, internal elastic lamina, fibrous cap and calcification provides additional knowledge to previously presented quantitative measurements of average plaque features. AFM imaging enhanced the results obtained with the use of vibrational microspectroscopies with additional topographical information of the sample. To the best of our knowledge, this is the first work which demonstrates that co‐localized measurement of atherosclerotic plaque with Raman, IR and AFM imaging provides a comprehensive insight into the biochemical markers of atherosclerotic plaques, and can be used as an integrated approach to assess vulnerability of the plaque. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)